Chapter Discovering the marina’s cultural heritage and cultural landscape - Martín, Ricardo (Proceedings e report, 2020)
Culture and heritage are relevant elements in the marinas’ landscape, and they could be competitive advantages in the management of these maritime facilities. This paper explores the marinas’ cultural heritage and cultural landscape, and it attempts to deep into the relationship between them. The identification and evaluation of these elements represents a main stage. It is also proposed three relationship models, ranging from integration, to strengthen and evolution, which enhance the image of the marina and its environment.